Modelagem de turbinas e reguladores de velocidade e seus impactos na simulação da regulação primária de frequência - Cenaqui, Thiago Carminatti (2018)
The change in the composition of the energy sources of the electrical systems, with the rapid and iminent growth of the participation of non-synchronous non-dispatchable renewable energy sources, is already a reality, mainly, in some developed countries. The gains and benefits for the environment are clear, but this new scenario presents big challenges and demands the realization of new studies focusing on the reliability of the operation and the planning of expansion of the electrical system. One of the aspects that will suffer a significant impact by the inverter-based sources, is the frequency quality. The focus of this work is not on the impact of reducing inertia, but on exploring some details of the conventional primary frequency control. In the studies of transient stability and frequency control, the use of appropriate electromechanical models of the generation plants are fundamental for obtaining robust results that can predict the actual behavior of the electrical system. This work presents the impact and importance of the representation, in electromechanical models, of certain characteristics of speed regulators and turbines for the evaluation of the primary frequency control. For this purpose, simulations are carried out in time domain in test systems, in which the implementation of the characteristics is made in isolated and combined forms, using metrics for sensitivity analysis of the frequency variation for a given event.